PENGARUH FITOESTROGEN DAGING BUAH KURMA RUTHAB (Phoenix dactylifera L.) TERHADAP SINKRONISASI SIKLUS ESTRUS MENCIT (Mus musculus L.) BETINA - NOVA LUSIANA (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2017)
Ruthab dates are believed to have benefits for couples who want to have a descendant because it has phytoestrogen content that has an important role in the female uterine blood vessels that can increase fertility. Phytoestrogens have estrogenic activity that has similar structures with natural estrogens. The purpose of this study was to investigate the effect of fitoestrogen of  date palm fruit (Phoenix dactylifera L.) to synchronize the estrous cycle in mice (Mus Musculus L.). Animals try to use 24 Balb / C starbine female mice. The test material in the form of extract of dates is given orally at doses of 260 mg/kg BB, 780 mg/kg BB and 1820 mg/kg BB. Data were analyzed by simple linier regression test with 5% significance level. The results showed a significant influence between the control and treatment group (R = 0.767) so that it can be concluded that the effect is caused by the action phytoestrogens  hormones in the content of dates.